Exploitation of Costa Rica’s Green Gold: Nuances of Deforestation between 1900 and 1950 - López López, Maximiliano (Revista de historia., 2021)
This work responds to the interest to know the scenario in which deforestation in the first half of the 20th century occurred in Costa Rica. Thus, the dynamics of deforestation are explored, as well as the discourse that justifies it, the nuances, and the contradictions that surfaced not only in state policy, but in the discourse of civil society, who was concerned about the exploitation of resources. This analysis reveals that during the first fifty years of the 20th century, Costa Rican society was torn between the uncertainty of the effects that deforestation might bring, the need to export natural resources as a way to contribute to national development, and the incipient idea regarding the possibility of conserving forests not only to protect the soil and water, but because they constituted also a source of future income through tourism.